Direito à cidade, valor de uso e valor de troca: proposta de framework para análise do planejamento urbano a partir do município de Curitiba - Pilarski, Mariel Mayer (2025)
Thinking about the city has become an increasingly complex task, as it must be understood not only as a population agglomeration, but as a dynamic social system, as highlighted by Robert Park. The concept of the right to the city, introduced by Henri Lefebvre and expanded by authors such as Milton Santos and David Harvey, remains fundamental to rethinking the urban environment as a space for equity, coexistence and collective well-being. However, the implementation of this right is still limited, often restricted to legal and architectural approaches, without considering territorial and social particularities. Urban policies face a crisis of paradigms and reveal fragility in the face of multiple social vulnerabilities. In Brazil, this scenario is aggravated by a disorderly urbanization process, marked by the absence of integrated planning and institutional precariousness. Urban space is shaped by disputes between social groups, and, often, the absence of political or technical decisions constitutes a form of decision-making that reinforces inequalities. This logic has prioritized exchange value — linked to mercantile logic — to the detriment of use value, which is related to collective well-being and quality of life in the territories. The research is applied in nature, has a qualitative approach and descriptive objective, with bibliographic and documentary procedures. Its central question is: what framework can be proposed to ensure the equitable distribution of the burdens and benefits of urbanization, based on the case of Curitiba, with an emphasis on the use value of urban space? The general objective is to propose an analytical framework for urban planning that prioritizes use value, promoting the realization of the right to the city. The specific objectives are: (i) to conceptualize the right to the city based on use value, contrasting it with exchange value, according to the theoretical frameworks adopted; (ii) to propose markers and indicators capable of ensuring this right and mitigating territorial exclusions; and (iii) to structure analytical categories that guarantee justice in the distribution of the burdens and benefits of urbanization. The proposal results in the formulation of a framework composed of three stages: social justice of space, sustainable development and capital accumulation. This structure is flexible, adapting to rapid urban transformations and technological advances, and is based on a set of exemplary markers and indicators. The right to the city is understood as a diffuse right, with prevalence of use value and equitable consumption of all urban spaces. The lack of updated and integrated data remains an obstacle to urban planning, and its valorization is essential. It also highlights the importance of using technologies and interdisciplinarity to break with paradigms and consolidate new analytical tools. Finally, the thesis contributes with a methodological and conceptual systematization that aims to expand the practical application of the right to the city, requiring the abandonment of consolidated beliefs and the adoption of use value as an ethical and social necessity to promote territorial justice.